Web-Based Knowledge Evolution for Thinking Green Transportation Using Expert Systems - M Abdelsalam, Hassan; Nazri Borhan, Muhammad; Milad, Abdalrhman; Imhimmed, Hamza; Y Y Alfakhri, Aboubaker; B.Z. Alshetwia, Abdurauf.; Atiq Ok Rahmat, Riza (International Journal of Engineering and Technology, 2018)
In many developing nations, it is difficult for development planners and novice engineers to determine the point of transportation service and usability based only on the master plan of the city. On the other hand, nowadays managers in the organizations use computerized support for making decisions on a day-to-day basis. The experts are capable of identifying problems easily and finding solutions fast but novice engineers are unable to do so. This expert system is designed to fulfill the gap that exist between the urban design experts and user who wish to use Green transportation system namely students, decision makers and engineers. Verification, process validation and comparison of the system with similar systems showed that the system is reliable and practical. In order to create the expert system, sources related to Expert system concerning transportation have been studied and interviews with experts have been conducted. The proposed expert system is developed using Visual Studio as the building tool and SQL as the query tool. The knowledge base of thinking green transportation [T Green T] includes three modules and each module may contain a number of sub-modules, parameters, strategies, and criteria. The system incorporate rules and images for various types of measurements. Lastly, several recommendations for maintaining and improving the system are suggested. The developmentâ€™s suitability can be characterized using websites of other modes of transportation such as bicycles and pedestrian traffic.Â Â